The Development of Discovery Learning Model to Reduce Science Misconceptions in Elementary School Students - Kiki Pratama Rajagukguk (LPPM STKIP AL MAKSUM, 2021)
This research was motivated by learning science at SD Negeri 118382 Torgamba where the teacher still used the lecture learning method, passive students and low learning completeness.This study aims to develop discovery learning models to reduce the misconceptions of science in elementary school students. This research was an R&D (Research and Development). The data collection techniques used were interviews, observation, questionnaires, and checklists. Data analysis techniques used qualitative and quantitative with the pretest-posttest group design. The model design is validated by experts and practitioners with the Delphi technique. The effectiveness of the learning model was tested using the t test. The results of the study after two trials showed that the discovery learning model have been valid, practical, and effective. The discovery learning model is stated to be valid because the assessment of all learning components conducted by validator meets the elements of validity. It is stated to be practical because the discovery learning component is fully implemented, and the ability of teachers to manage learning is at the high category. It is stated to be effective because the misconceptions of Science student are in the medium category. The activities of students in learning are fulfilled the ideal time achievement, and the results of the students’ questionnaire give the positive respond to discovery inquiry learning. It is concluded that the discovery learning model to reduce the misconception of Science students meets the criteria of valid, practical, and effective.